PENERAPAN KOMUNIKASI TERAPEUTIK PADA ANAK PENYANDANG DOWN SYNDROME MELALUI PELAYANAN TERAPI WICARA DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Resya Nur Intan Putri; S Bekti Istiyanto (Jurnal Dakwah Risalah, 2019)
This study talks about the therapeutic communication process carried out by medical personnel (speech therapists) with patients with special needs who are specified in persons with Down syndrome at Prof. RSUD. Dr. Margono Soekarjo Purwokerto. This study aims to determine the process or method of conducting therapeutic communication by speech therapists with pediatric patients with Down syndrome in Prof. RSUD. Dr. Margono Soekarjo Purwokerto. The method used in this study is an explorative qualitative method. The results of this study indicate that to conduct a therapeutic communication with pediatric patients can be done using several methods in language therapy, for example such as modeling and self talk-parallel talk methods. Furthermore, there is a therapeutic communication process carried out by a therapist consisting of the stages of pre-interaction, introduction, orientation, work, and termination. In therapeutic communication that is interwoven there is also the exchange of messages and obstacles experienced by therapists in carrying out the process.